2009
DOI: 10.1111/j.1460-9592.2009.03046.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the glidescope video laryngoscope in pediatric patients

Abstract: The GlideScope video laryngoscope is equally suitable to facilitate orotracheal intubation in pediatric patients compared to the Macintosh laryngoscope with respect to intubation time and laryngeal trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 15 publications
1
37
0
Order By: Relevance
“…Kim et al 9 were able to demonstrate an improvement in view in 203 pediatric patients with normal airway anatomy using the GlideScope compared with direct laryngoscopy with the cost of a prolonged time to intubate. In a study of Redel et al, 13 the GlideScope provided slightly better views to the glottis in comparable times in 60 children, 10 years or younger with normal airway anatomy. The GlideScope has been used in addition in children with known difficult intubation or difficult airway anatomy.…”
Section: Discussionmentioning
confidence: 93%
“…Kim et al 9 were able to demonstrate an improvement in view in 203 pediatric patients with normal airway anatomy using the GlideScope compared with direct laryngoscopy with the cost of a prolonged time to intubate. In a study of Redel et al, 13 the GlideScope provided slightly better views to the glottis in comparable times in 60 children, 10 years or younger with normal airway anatomy. The GlideScope has been used in addition in children with known difficult intubation or difficult airway anatomy.…”
Section: Discussionmentioning
confidence: 93%
“…In a study of 203 children, the Glidescope provided a comparable or better laryngeal view than conventional laryngoscopy, but took a longer time to achieve intubation [7]. Conversely, Redel et al reported similar intubation times in a randomised study of 60 children [8].…”
mentioning
confidence: 99%
“…Numerous studies have already shown VL to be successful in adults and children, but what our study offers is a broadening of the GSC's utility to include neonates and infants (4,13,14). Much of the success seen with the GSC can be attributed to the improved view offered, which is a result of the improved optics and the decreased profile of the blade (1).…”
Section: Disussionmentioning
confidence: 83%
“…The role of VL in pediatric anesthesia continues to grow at an exponential rate. Numerous studies have demonstrated the ability of VL to provide improved glottic views and comparable intubation times in comparison to DL in the pediatric population (3)(4)(5)(6). Unfortunately, some of these studies have been limited by small sample sizes and a lack of focus on neonates and infants (6).…”
Section: Introductionmentioning
confidence: 99%